Interdisciplinarity at the journal and specialty level: The changing knowledge bases of the journal cognitive science - Leydesdorff, Loet; Goldstone, Robert L. (Journal of the American Society for Information Science and Technology, 2014)
Using the referencing patterns in articles in Cognitive Science over three decades, we analyze the knowledge base of this literature in terms of its changing disciplinary composition. Three periods are distinguished: (A) construction of the interdisciplinary space in the 1980s, (B) development of an interdisciplinary orientation in the 1990s, and (C) reintegration into “cognitive psychology” in the 2000s. The fluidity and fuzziness of the interdisciplinary delineations in the different visualizations can be reduced and clarified using factor analysis. We also explore newly available routines (“CorText”) to analyze this development in terms of “tubes” using an alluvial map and compare the results with an animation (using “Visone”). The historical specificity of this development can be compared with the development of “artificial intelligence” into an integrated specialty during this same period. Interdisciplinarity should be defined differently at the level of journals and of specialties.